Der - som formelt subjekt i dansk - Szubert, Andrzej (Folia Scandinavica Posnaniensia, 2007)
The article is an attempt at describing the use and meaning of one of the small but meaningful Danish words - der. It endeavours to present the syntactic role and the semantic meaning of der in a sentence. The final part of the article contains a comparison of der and del, which can be used similarly in some functions, as in the det-kl0vning compared to the der-kløvning.